Sustainable Urban Agriculture in Cuba - Koont, Sinan, 1943- (Book collections on Project MUSE., 2011)
Sinan Koont has spent the last several years researching urban agriculture in Cuba, including field work at many sustainable farms on the island. He tells the story of why and how Cuba was able to turn to urban food production on a large scale with minimal use of chemicals, petroleum, and machinery, and of the successes it achieved--along with the continuing difficulties it still faces in reducing its need for food imports.